Are two tax rates better than one? - Felix R. FitzRoy; Jim Jin (Institute for the Study of Labor (IZA), 2009)
Should two-band income taxes be progressive given a general income distribution? We provide a negative answer under utilitarian and max-min welfare functions. While this result clarifies some ambiguities in the literature, it does not rule out progressive taxes in general. If we maximize total or weighted utility of the poor, as often intended by the society, progressive taxes can be justified, especially when the 'rich' are very rich. Under these objectives we obtain necessary conditions for progressive taxes, which only depend on aggregate features of income distributions. The validity of these conditions is examined using plausible income distributions.
urn:nbn:de:101:1-20090605244
Keywords: H20; D40; 330; Progressive tax; utilitarian; max-min; help the poor; Einkommensteuer; Steuerprogression; Einkommensumverteilung; Utilitarismus; Wohlfahrtseffekt; Theorie